ABCA4 Gene Screening in a Chinese Cohort With Stargardt Disease: Identification of 37 Novel Variants - Hu, Fang-Yuan; Li, Jian-kang; Gao, Feng-Juan; Qi, Yu-He; Xu, Ping; Zhang, Yong-Jin; Wang, Dan-Dan; Wang, Lu-Sheng; Li, Wei; Wang, Min; Chen, Fang; Shen, Si-Mai; et al. (Frontiers in Genetics, 2019)
Purpose: To clarify the mutation spectrum and frequency of ABCA4 in a Chinese cohort with Stargardt disease (STGD1). Methods: A total of 153 subjects, comprising 25 families (25 probands and their family members) and 71 sporadic cases, were recruited for the analysis of ABCA4 variants. All probands with STGD1 underwent a comprehensive ophthalmologic examination. Overall, 792 genes involved in common inherited eye diseases were screened for variants by panel-based next-generation sequencing (NGS). Variants were ﬁltered and analyzed to evaluate possible pathogenicity. Results: The total variant detection rate of at least one ABCA4 mutant allele was 84.3% (129/153): two or three disease-associated variants in 86 subjects (56.2%), one mutant allele in 43 subjects (28.1%), and no variants in 24 subjects (15.7%). Ninety-six variants were identified in the total cohort, which included 62 missense (64%), 15 splicing (16%), 11 frameshift (12%), 6 nonsense (6%), and 2 small insertion or deletion (2%) variants. Thirty-seven novel variants were found, including a de novo variant, c.4561delA. The most prevalent variant was c.101_106delCTTTAT (10.5%), followed by c.2894A>G (6.5%) and c.6563T>C (4.6%), in STGD1 patients from eastern China. Conclusion: Thirty-seven novel variants are detected using panel-based NGS, including one de novo variant, further extending the mutation spectrum of ABCA4. The common variants in a population from eastern China with STGD1 are also identified.